eLingua : Issue 1 : July 2020 / Academy of Language Studies - Chone, Liaw Shun; Kudus, Nazima Versay; Tazijan, Farina Nozakiah; Aboo Bakar, Rofiza; Yih, Mah Boon; Affendy Lee, Noor Azli; Mohd Amin, Noraziah; Zulkifli, Che Nooryohana; Razali, Wan Noorli; Fen, Ong Sheau; Mohd Yusof, Noor Laili; Giap, Lim Soo (Academy of Language Studies, 2020)
1. UiTM 2025 Strategic Plan – Forging Ahead 2. A Chance to Meet the Author Online 3. Academy of Language Studies Universiti Teknologi MARA Cawangan Pulau Pinang Invited as Guest Lecturers For a One Week Event in Tanjungpura University, Pontianak, Indonesia (UNTAN) 4. Profesor Dr. Salmiah Kasolang: Antara Pentadbir dan Pemacu Semangat 5. Special Column ‘A Tribute to Puan Sabariah Binti Muhamad’ 6. ‘Getting to know you more’ Featuring ... Ts. Dr. Mohd Rozaiman Bin Aziz 7. LINK-IT: a Board Game for Mastering English Linkers 8. UiTM Webitors won their first Medal in the InIIC Series 1/2020 9. Baba & Nyonya in Penang 10. Declutter to feel better! 11. Home garden 12. Perayaan hantu (Hungry ghost festival) 13. Emoticon as a communicator 14. Penggunaan Nombor-nombor dalam Pembentukkan Kata Masa Bahasa Mandarin 15. ACHEH: 15 TAHUN SELEPAS TSUNAMI KRISMAS 16. Superstar Libra Cruise: Pelayaran Mewah ala Titanic 17. This Solace is All We Need 18. We are One for this Battle 19. Malaysia and Covid-19